2002
DOI: 10.1016/s0304-3959(02)00274-9
|View full text |Cite
|
Sign up to set email alerts
|

Tailored cognitive-behavioral therapy in early rheumatoid arthritis for patients at risk: a randomized controlled trial

Abstract: Recent developments in chronic pain research suggest that effectiveness of cognitive-behavioral therapy (CBT) may be optimized when applying early, customized treatments to patients at risk. For this purpose, a randomized, controlled trial with tailor-made treatment modules was conducted among patients with relatively early rheumatoid arthritis (RA disease duration of <8 years), who had been screened for psychosocial risk profiles. All participants received standard medical care from a rheumatologist and rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
204
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(224 citation statements)
references
References 62 publications
6
204
0
14
Order By: Relevance
“…Our results are consistent with other psychotherapeutic interventions that demonstrate improvement in RA disability, pain, depression, and/or coping efficacy 5,6,7,31,32 . Reductions in disease activity and joint inflammation have been reported after cognitive behavioral therapy (CBT), particularly in those subjects with earlier-onset RA 4,9,10,11,14,32 .…”
Section: Rheumatologysupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with other psychotherapeutic interventions that demonstrate improvement in RA disability, pain, depression, and/or coping efficacy 5,6,7,31,32 . Reductions in disease activity and joint inflammation have been reported after cognitive behavioral therapy (CBT), particularly in those subjects with earlier-onset RA 4,9,10,11,14,32 .…”
Section: Rheumatologysupporting
confidence: 90%
“…A number of psychobehavioral interventions have been shown to be effective in improving coping efficacy and other outcomes in patients with RA 4,5,6,7,8,9,10,11 . Cognitive behavioral interventions, in particular, have reduced pain, joint inflammation, physical disability, and depression 5,6,9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In case of moderate adjustment problems, self-management interventions could sufficiently improve functioning by combining education with some cognitive-behavioral principles such as relaxation, problem solving, and goal setting [2]. For more severe adjustment problems, different evidence-based personalized therapist-guided treatments have become available for diverse patient groups and also include disease-generic approaches that encompass a broad variety of treatment modules of the most relevant areas of functioning across diseases and different cognitive-behavioral techniques and assignments that can be flexibly applied [68,89,90]. Within such tailored treatments, the content of the treatment (e.g., choice of modules to work on and specific topics or assignments within each module) is based on the elaborate screening in combination with the patient priorities and judgment of the therapist.…”
Section: Moderate Adjustment Problemsmentioning
confidence: 99%
“…It has been shown that patient education or self-management is sufficient for patients in the early adjustment phase of the disease or who show mild adjustment problems and also strengthens patient empowerment [3,88], whereas more intensive treatments are most beneficial for patients who show heightened distress levels [68,85]. Likewise, there is some evidence that personalized or tailored treatment possibly leads to stronger and longer-lasting effects than standardized treatments in addition to increased treatment motivation, adherence, and patient satisfaction and decreased attrition rates in both mental and physical health conditions and in both face-to-face and internet-based interventions [3,85,89,91e93].…”
Section: Moderate Adjustment Problemsmentioning
confidence: 99%